Teachers' Self-Efficacy in Dyscalculia: Development and Psychometric Validation of a New Scale - Oflaz, Gulcin; Polat, Kubra; Mutlu, Yilmaz; Cam, Zekeriya (Mdpi, 2026)
The aim of this study is to develop a valid and reliable scale for measuring the self-efficacy of primary school and mathematics teachers regarding dyscalculia. Grounded in Bandura's Social Cognitive Theory, the study followed established scale development procedures. In the initial phase, a pool of 42 items was generated to assess teachers' self-efficacy regarding dyscalculia. The items were reviewed by a panel of seven experts in the fields of psychometrics, mathematics education, special education, and psychology to ensure content validity. Based on expert evaluations, four items were removed due to overly technical phrasing that could lead to misinterpretation, reducing the pool to 38 items. Subsequently, Exploratory Factor Analysis (EFA) conducted with 273 teachers indicated that four additional items exhibited inadequate factor loadings or problematic cross-loadings; these items were also excluded. The resulting Dyscalculia Self-Efficacy Scale (DSES) comprises 34 items organized into four factors: Dyscalculia Symptoms, Providing Psychological Support to Children with Dyscalculia, Diagnosing Dyscalculia, Providing Support in the Teaching Process. Confirmatory Factor Analysis conducted with a separate sample of 242 teachers yielded strong model fit indices, supporting the construct validity of the scale. The overall scale demonstrated high internal consistency (Cronbach's alpha = 0.980, McDonald's omega = 0.980). Correlation analyses with established instruments provided evidence of convergent and discriminant validity. The findings indicate that the DSES is a valid and reliable instrument for assessing teachers' self-efficacy regarding dyscalculia.
Keywords: Dyscalculia; Teacher Self-Efficacy; Scale Development; Mathematics Learning Difficulties; Teacher Competencies